Becoming More Rugged and Better Resourced: The R2 Resilience Program’s© Psychosocial Approach to Thriving - Ungar, Michael; Jefferies, Philip (Frontiers in Psychology, 2021)
The past decade has seen growing interest in interventions that build resilience as a complementary practice to trauma-informed care. From school-based programs focused on self-regulation and academic success to programs that support the well-being of disadvantaged populations or healthcare workers at risk of burnout, the concept of resilience is being used most commonly for programming that builds the capacity of individuals to adapt under conditions of adversity. Critiques have raised concerns that resilience-promoting programs demonstrate bias toward changing individual-level factors such as cognitions (e.g., mindfulness and grit), behavior (e.g., expressing gratitude and changing personal routines), or attachments (e.g., feeling secure in relationships) which help people adapt to socially toxic situations without changing access to the resources they require to overcome exposure to adverse psychosocial factors. This trend belies advances to the theory of resilience which support a more contextualized, multisystemic understanding of how external protective factors (resources) enhance individual qualities (ruggedness) and vice versa. Building on a multisystemic description of resilience, the R2 Resilience Program© was developed and piloted with six different populations ranging from clients of urban social services to workers in a long-term care facility, managers in the health care sector, staff of a Fortune 500 corporation, students in a primary to grade 12 school, and adult volunteers affiliated with an international NGO. Focused on building both individual ruggedness and enhancing people’s resources (the two Rs), the program provides contextualized content for each population by selecting from 52 resilience promoting factors with a strong evidence base to create training curricula that enhance the personal qualities and social, physical, and institutional resources most likely to support resilience. This paper reviews the justification for a multisystemic approach to designing resilience interventions and then explains the process of implementation of the R2 program. Preliminary findings are reported, which suggest the program is experienced as effective, with evaluations ongoing.